A versatile prototype plasma reactor for water treatment supporting different discharge regimes. (13th June 2018) - Ceriani, Elisa; Marotta, Ester; Schiorlin, Milko; Ren, Xianwen; Ceretta, Claudio; Gobbo, Renato; Tampieri, Francesco; Paradisi, Cristina
Abstract: A comparative evaluation is reported of the performance of different discharge regimes—AC powered dielectric barrier discharge (DBD) and DC powered corona discharge of positive (DC+) and negative (DC−) polarity—implemented within the same reactor, a benchtop prototype for an advanced oxidation stage in water treatment. For all three modes of operation, DBD, DC+  and DC−, the reactor performance was tested using phenol as model pollutant and determining the process energy efficiency ( k E and G 50 ), kinetics ( t 1/2 ), nitrated byproducts and extent of mineralization to CO2 . Finally, comparison with a smaller DBD reactor of similar configuration previously used in our lab (Marotta et al 2011 Plasma Proc. Polym .8 867) shows that scaling up was carried out successfully and holds promise for larger scale applications.